Accurate Fe3+/Fetot ratio from XAS spectra at the Fe K-edge. (October 2020) - Galdenzi, Federico; Ventura, Giancarlo Della; Cibin, Giannantonio; Macis, Salvatore; Marcelli, Augusto
Abstract: A new approach to extract accurate information on the Fe oxidation state has been tested on three different Fe-rich amphiboles annealed at 194–520 °C. The method is based on the analysis of the pre-edge structure of the X-ray absorption spectra at the Fe-K edge. The pre-edge band is deconvolved into four Gaussian components where the integrated intensities of the pairs of lower- and higher-energy bands are related to the ferrous to ferric ion ratio. These Fe 3+ /Fetot ratios have been compared with those obtained with independent techniques (X-ray diffraction and Mossbauer spectroscopy) on the same samples. The experimental data allowed establishing a calibration curve that is in good agreement with a recent statistical analysis based on spectroscopic data for the same type of minerals. The method could be extended to the analysis of other complex systems containing both Fe 3+ and Fe 2+ in octahedral coordination or to study the dynamics of iron under non-ambient conditions. Highlights: Extraction of the Fe 3+ /Fetot ratio from the pre-edge structure at the Fe K-edge. Fitting of the pre-edge with 4 Gaussians representative of ferric and ferrous ion. Calibration line combining the pre-edge analysis and Mössbauer spectroscopy data. Method suitable to investigate Fe dynamics in complex systems such as amphiboles.